Sodium citrate supplementation enhances tennis skill performance: a crossover, placebo-controlled, double blind study. Issue 1 (1st August 2019) - Cunha, Vivian C. R.; Aoki, Marcelo S.; Zourdos, Michael C.; Gomes, Rodrigo V.; Barbosa, Wesley P.; Massa, Marcelo; Moreira, Alexandre; Capitani, Caroline D.
Abstract: Background: The efficacy of sodium citrate supplementation (SC) in exercise performance is unclear. Therefore, the aim of this study was to investigate the effect of SC on skilled tennis performance. Methods: Ten Brazilian nationally-ranked young male tennis players (age: 17 ± 1 yrs.; stature: 176.7 ± 5.2 cm; body mass: 68.4 ± 7.9 kg) participated in this crossover, placebo-controlled, double-blind study. Upon arrival, at baseline, in both experimental sessions blood was collected, then subjects ingested either sodium citrate (SC - 0.5 g . kg −1 BM in capsules of 500 mg) or a placebo (PLA). Two hours later, pre-match blood was collected then skills tests (skill tennis performance test - STPT, repeated-sprint ability shuttle test - RSA) were performed followed by a 1-h simulated match. Immediately following the match, blood was again collected, and STPT, and RSA were administered. Results: All metabolic parameters (i.e. base excess, pH, bicarbonate, and blood lactate) increased ( p < 0.001) from baseline to pre-match and post-match in SC condition. Each metabolic parameter was greater (p < 0.001) in SC compared to PLA condition at both pre- and post-match. The SC condition elicited a greater ( p < 0.01) shot consistency at post-match in the STPT vs. PLA condition (SC: 58.5 ± 14.8% vs. PLA: 40.4 ± 10.4%). A greater ( p < 0.001) amount of games won was observed in the simulated match for SC condition vs. PLA condition (SC: 8.0 ± 1.6 vs. PLA: 6.0 ± 1.7). Additionally, the games won during the simulated match in SC condition was positively correlated with percentage shot consistency (r = 0.67, p < 0.001). Conclusions: The current findings suggest that SC supplementation is an effective ergogenic aid to enhance skilled tennis performance.